Partial revision of the Afrotropical Ballini, with the description of seven new genera (Araneae: Salticidae) - Azarkina, Galina N.; Haddad, Charles R. (Zootaxa, 2020)
The jumping spider tribe Ballini is reviewed in the Afrotropical Region. The genera Afromarengo Benjamin, 2004 and Goleta Peckham & Peckham, 1894 are redefined. In Afromarengo, A. coriacea (Simon, 1900) is illustrated and A. ghanaensis sp. nov. (♀, from Ghana) and A. ugandensis sp. nov. (♂♀, from Uganda and D.R. Congo) are newly described. For Goleta, the type species, Goleta workmani (Peckham & Peckham, 1885), is redescribed from both sexes. Seven new genera and twelve new species are described, including three monotypic genera, Ballagascar gen. nov., with B. insularis (Peckham & Peckham, 1885) comb. nov. (ex Colaxes Simon, 1900) from Madagascar (♂♀) as the type species; Mondeku gen. nov., with M. albopilosum sp. nov. (♂♀, from Kenya) as the type species; and Oviballus gen. nov., with O. vidae sp. nov. (♂♀, from South Africa) as the type species. We also describe Planamarengo gen. nov., with P. bimaculata (Peckham & Peckham, 1903) comb. nov. (ex Afromarengo) from South Africa (♂♀) as the type species, as well as P. gatamaiyu sp. nov. (♂, from Kenya) and P. kenyaensis sp. nov. (♂♀, from Kenya); Propiomarengo gen. nov., with P. plana (Haddad & Wesołowska, 2013) comb. nov. (ex Afromarengo) from South Africa (♀) as the type species, as well as P. foordi sp. nov. (♂, from South Africa); Tenuiballus gen. nov., with T. minor sp. nov. (♂, from South Africa) as the type species, and also including T. coronatus sp. nov. (♂, from South Africa); and Wandawe gen. nov., with W. benjamini (Wesołowska & Haddad, 2013) comb. n. (ex Colaxes) from South Africa (♂♀) as the type species, and also including W. australe sp. nov. (♂♀, from South Africa) and W. tigrinа sp. nov. (♂♀, from Kenya and Uganda). A new combination for Copocrossa albozonata Caporiacco, 1949, Afromarengo albozonata comb. nov. is provided, and the name A. albozonata is treated as a nomen dubium. A new species of Padilla Peckham & Peckham, 1894, a genus only known from the Afrotropical Indian Ocean islands, P. wandae sp. nov. (♂♀, from Madagascar), is described. New data and illustrations for Sadies Wanless, 1984, as well as two Asian species of Colaxes, are provided. The recently revised Pachyballus Simon, 1900 and Peplometus Simon, 1900 are not treated further. A key to the genera of Afrotropical Ballinae is presented, as well as new data on their natural history, biogeography, and a discussion of the evolution of mimicry of various arthropod groups by balline jumping spiders. A putative synapomorphy and the new composition of Ballini sensu novo are proposed.